2020
DOI: 10.3389/fchem.2020.597980
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solvents' Polarity on the Physicochemical Properties and Photocatalytic Activity of Titania Synthesized Using Deinbollia pinnata Leaves

Abstract: Nanotechnology is one of the most interesting areas of research due to its flexibility to improve or form new products from nanoparticles (NPs), and as a fast, greener, more eco-friendly and sustainable solution to technological and environmental challenges. Among metal oxides of photocatalytic performance, the use of titania (TiO2) as photocatalyst is most popular due to its unique optical and electronic properties. Despite the wide utilization, the synthesis of TiO2 NPs bears many disadvantages: it utilizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The obtained results showed that 97.53% of MO was degraded after 150 min of UV irradiation. These data indicate that a high performance can be reached within a short time thanks to the enhanced charge carrier's separation and increased surface area [35].…”
Section: Green Synthesis Of Tio 2 and Zno Nanoparticles Based On Vari...mentioning
confidence: 75%
See 2 more Smart Citations
“…The obtained results showed that 97.53% of MO was degraded after 150 min of UV irradiation. These data indicate that a high performance can be reached within a short time thanks to the enhanced charge carrier's separation and increased surface area [35].…”
Section: Green Synthesis Of Tio 2 and Zno Nanoparticles Based On Vari...mentioning
confidence: 75%
“…The obtained suspension was rinsed with ethanol and centrifuged at 10,000 rpm for 30 min. Finally, the samples were dried (95 • C for 24 h) and calcined at 500 • C for 5 h. For the characterization different techniques were used: XRD, SEM, EDX, UV-Vis spectrometry, BET, and FTIR [35]. The XRD results confirmed the anatase phase of TiO 2 NPs in great purity with average crystal size in the range of 19-21 nm.…”
Section: Green Synthesis Of Tio 2 and Zno Nanoparticles Based On Vari...mentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, it does not require high pressure or high temperature, and above all, it is not harmful to the environment [14]. Plants, bacteria, fungi, algae, and actinomycetes can all be used to produce NPs, and have been proven to improve the photocatalytic and pharmacological characteristics of the synthesized NPs [15]. According to Nadeem et al [16], plants, particularly the leaves, are the most suitable for NPs synthesis because they are rich in metabolites, which are mainly involved in the reduction process.…”
Section: Introductionmentioning
confidence: 99%
“…Thymus migricus and Alcea [36], Tamarindus indica [37], Punica granatum, Lippia citriodora [38], Deinbollia pinnata [15], and Prunus domestica L. [5].…”
Section: Introductionmentioning
confidence: 99%